Assignment Model for Leds and Photodetectors in a Vlc System - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2020)
The localization of people has been problem widely studied with several communication technologies such as RFID and WiFi. However, the particular behavior of systems based on Visible Light Communication (VLC) needs an adjustment or proposition of new forms of localization, considering the features of the system such as the range of transmission and covering of the communication. This work proposes a covering algorithm for the localization of people using VLC, which was validated with a simulation, using as a case the communication in a tunnel. The proposed model solves the problem of assigning LEDs, using a Set Covering algorithm. Thus, it optimizes the capacity of the canal and complies with the restrictions of trilateration and efficiency. © 2020 IEEE.